1997
DOI: 10.1074/jbc.272.17.11408
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Characterization of a Novel Phospholipase D Complementary DNA from Rat Brain

Abstract: Here we report the cloning and characterization of cDNA for a different type of PLD (rat PLD2 (rPLD2)) from rat brain. We synthesized highly degenerate amplimers corresponding to the conserved regions of eukaryote PLDs and performed polymerase chain reaction on a rat brain cDNA library. Using the amplified sequence as the probe, we cloned a rat brain cDNA clone that contained an open reading frame of 933 amino acids with an M r of 105,992. The deduced amino acid sequence showed significant similarity to hPLD1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
166
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(182 citation statements)
references
References 45 publications
16
166
0
Order By: Relevance
“…In the absence of further evidence, some workers have suggested that the purified activity may have been related to PLD2 (40). Two related polyphosphoinositolactivated PLD isoforms have been cloned on the basis of yeast PLD sequences (262,266) and are known as PLD1 (120 kDa) (81, 82, 122, 187) and PLD2 (106 kDa) (43,130). The catalytic site contains two H(x) K(x) 4 D (HKD) domains separated by variable nonactive site sequences.…”
Section: Substrates For Lppmentioning
confidence: 99%
“…In the absence of further evidence, some workers have suggested that the purified activity may have been related to PLD2 (40). Two related polyphosphoinositolactivated PLD isoforms have been cloned on the basis of yeast PLD sequences (262,266) and are known as PLD1 (120 kDa) (81, 82, 122, 187) and PLD2 (106 kDa) (43,130). The catalytic site contains two H(x) K(x) 4 D (HKD) domains separated by variable nonactive site sequences.…”
Section: Substrates For Lppmentioning
confidence: 99%
“…1) (1,4,(13)(14)(15)(16)(17). In the CDP-DAG pathway, PC is synthesized from CDP-DAG via the reactions catalyzed by PS synthase (18 -20), PS decarboxylase (21-23), PE methyltransferase (24, 25), and phospholipid methyltransferase (24,26). In the CDP-choline branch of the Kennedy pathway, PC is synthesized from choline via the reactions catalyzed by choline kinase (27), phosphocholine cytidylyltransferase (28), and choline phosphotransferase (29,30).…”
mentioning
confidence: 99%
“…However, unlike mutants defective in the CDP-DAG pathway (23)(24)(25)(26)(43)(44)(45)(46), these Kennedy pathway mutants do not exhibit any auxotrophic requirements (36,47). Moreover, even in the absence of the Kennedy pathway, the cki1⌬ eki1⌬ (47) and cpt1 ept1 (36) mutants have an essentially normal complement of phospholipids including PC.…”
mentioning
confidence: 99%
“…In reconstitution systems, the catalytic activity of recombinant hPLD1, purified PLD, or enriched PLD fractions was synergistically increased by the presence of ARF, rho small GTPases, and protein kinase C␣ (PKC␣). Another protein with PLD activity and 60% homology to PLD1 was recently cloned in mouse, rat, and human tissues and named PLD2 [7][8][9][10]. Mouse PLD2 was found to be insensitive to small GTPases but required PIP2 for maximal activation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another protein with PLD activity and 60% homology to PLD1 was recently cloned in mouse, rat, and human tissues and named PLD2 [7][8][9][10]. Mouse PLD2 was found to be insensitive to small GTPases but required PIP2 for maximal activation [8]. In contrast, human PLD2 was found to be sensitive to ARF, although to a lesser extent than hPLD1 [10].…”
Section: Introductionmentioning
confidence: 99%